Multilayered structure and enhanced thermoelectric properties of Bi1.5Sb0.5Te3 film with preferential growth. Issue 12 (17th September 2013) - Tan, Ming; Deng, Yuan; Hao, Yanming
<x xml:space="preserve">Abstract</x> In this paper, uniquely (0 1 5)‐preferential growth plane and alternating stress field can favorably influence the carrier and phonon transport properties of multilayered films. The p‐type Bi1.5Sb0.5Te3 multilayered film has been successfully fabricated by a simple thermal co‐evaporation technique. The composition, microstructure, and in‐plane thermoelectric (TE) properties of films have been characterized and measured, respectively. The measurement results show that the multilayered Bi1.5Sb0.5Te3 film is (0 1 5)‐preferential growth. The multilayered structure film is composed of the (0 1 5)‐oriented and the ordinary nanolayers. The properties of the multilayered Bi1.5Sb0.5Te3 film has been significantly enhanced in comparison with those of the highly (0 1 5)‐oriented and the ordinary Bi1.5Sb0.5Te3 films. The multilayered Bi1.5Sb0.5Te3 film with a TE dimensionless figure‐of‐merit ZT = 1.28 was obtained at room temperature. The transport mechanism of multilayered structure is proposed and investigated. The internal strain field and (0 1 5)‐preferential growth plane are the main reasons for the properties enhancement observed in the multilayered Bi1.5Sb0.5Te3 film. Introduction of such uniquely (0 1 5)‐preferential growth plane and alternating stress field into TE films is therefore a very promising approach.